Validation of the Positive Emotion Scale (PES-14) in Indonesian adolescents: a study in the Towani Tolotang Hindu community - Rustam, Husnul Khotimah; Hanafi, Yusuf; Farida, Ika Andrini; Mustakim, Sitti Salina (Behi Academy Publications, 2026)
Objective: The purpose of this study is to develop instruments for measuring positive emotions in the Towani Tolotang Hindu community in Indonesia. Methods and Materials: The selection of respondents from the Towani Tolotang Hindu youth in Sidenreng Rappang Regency was motivated by the community's strong enthusiasm for this religion, which is based on ancient Bugis beliefs. This study developed a Positive Emotion Scale for use in Hindu adolescents. This scale was validated through confirmatory factor analysis (CFA) in 568 late adolescents. Findings: CFA supported a three-factor structure (recurrent positive psychological states; social connectedness; physical refreshed energy) with standardized loadings ranging approximately from 0.54 to 0.83 (p<0.001). Model fit was acceptable/borderline (CFI=0.935; TLI=0.921; NFI=0.919; GFI=0.990; RMSEA=0.080), while SRMR was high (0.143), suggesting room for model improvement. Reliability was satisfactory to high (α up to 0.89; ω up to 0.92), and AVE ranged from 0.426 to 0.560. Conclusion: The Indonesian PES-14 shows generally supportive evidence of validity and reliability for Towani Tolotang Hindu adolescents, but the elevated SRMR indicates that refinement (e.g., item rewording, correlating theoretically justified errors, or alternative models) and additional validity evidence are recommended.